Spirituality As A Protective Factor Against Substance Abuse In High-Risk Communities - Amin Al Haadi Shafie; Nur Faizah Abdul Kahar; Dini Farhana Baharudin; Nurhafizah Mohamad Yasin (HRMARS, 2026)
Indexed by ERA